Longitudinal analysis of school-workplace cooperation in vocational training - exploring time-invariant and time-varying predictors - Beifang Ma [Verfasser]; Winther, Esther [Verfasser] (My University, 2025)
“School-workplace cooperation is a unique research field within the dual training system, where trainees’ subjective experience of this cooperation is crucial for investigating training quality. In this study, we tracked 458 industrial administrative assistant trainees throughout their entire training period and modeled changes in their experience of one organizational and two pedagogical dimensions of school-workplace cooperation over time and across individual trainees. Using a Latent Growth Model (LGM), we included both time-invariant and time-varying predictors to explain the growth dynamics of these dimensions of trainees’ experience of school-workplace cooperation. The results show that all three dimensions have unique growth dynamics over time and across individual trainees. The way predictors influence their growth also differs significantly from each other. Among the dimensions, the practical relevance of school learning shows a decline and is the most sensitive to predictors. The integration of specialized knowledge has seen an increase but can rarely be explained by factors included in this study. The transparency and organization of training dimension has remained relatively stable.” (authors’ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.4.1 Lernortkooperation; 370; Berufsausbildung; Industriekaufmann; Ausbildungsqualität; Lernortkooperation; Befragung; Learning Analytics